Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Mémoire du Conseil catholique d’expression anglaise sur la création de réseaux locaux de services de santé et de services sociaux à Montréal - Allmand, Warren (Conseil catholique d’expression anglaise, 2004)

Baseline Data Report 2003-2004 : Regional Profiles of English-speaking Communities - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2004)
This report includes a general overview of the situation of the English‐speaking population in a minority context as well as the particular demographic characteristics and vitality issues which vary tremendously across its 16 administrative health regions • The profile of each region is organized to highlight a broad range of factors that have been shown to have a strong influence on the health status of a population and ultimately the quality of life of its constituents • These health determinants are located in the context of national, provincial and regional demographic characteristics with comparisons between Anglophone minority and Francophone majority populations within a regional territory • Where significant, and possible, the tendencies of certain factors over time will be underlined • The commonalities among English‐speaking regional communities as well as the distinct features of each in terms of demographics, experiences, and attitudes are highlighted throughout this process and summarized in terms of key strengths and needs to be targeted in considering future health and social service initiatives
Keywords: Official Language Minority Community (OLMC)

Choices through Knowledge: Community training in palliative care - Jones, Jo-Ann; Quebec Association for Adult Learning (QAAL) (2004)